Molecular epidemiology of tuberculosis in the Somali region, eastern Ethiopia - Worku, Getnet; Gumi, Balako; Mohammedbirhan, Binyam; Girma, Musse; Sileshi, Henok; Hailu, Michael; Wondimu, Amanuel; Ashagre, Wondimu; Tschopp, Rea; Carruth, Lauren; Ameni, Gobena (Frontiers in Medicine, 2022)
Background Tuberculosis (TB) is one of the leading causes of morbidity and mortality in low-income countries like Ethiopia. However, because of the limited laboratory infrastructure there is a shortage of comprehensive data on the genotypes of clinical isolates of Mycobacterium tuberculosis (M. tuberculosis) complex (MTBC) in peripheral regions of Ethiopia. The objective of this study was to characterize MTBC isolates in the Somali region of eastern Ethiopia. Methods A cross-sectional study was conducted in three health institutions between October 2018 and December 2019 in the capital of Somali region. A total of 323 MTBC isolates (249 from pulmonary TB and 74 from extrapulmonary TB) were analyzed using regions of difference 9 (RD 9)-based polymerase chain reaction (PCR) and spoligotyping. Results Of the 323 MTBC isolates, 99.7% (95% CI: 99.1–100%) were M. tuberculosis while the remaining one isolate was M. bovis based on RD 9-based PCR. Spoligotyping identified 71 spoligotype patterns; 61 shared types and 10 orphans. A majority of the isolates were grouped in shared types while the remaining grouped in orphans. The M. tuberculosis lineages identified in this study were lineage 1, 2, 3, 4, and 7 with the percentages of 7.4, 2.2, 28.2, 60.4, and 0.6%, respectively. Most (87.9%) of the isolates were classified in clustered spoligotypes while the remaining 12.1% isolates were singletons. The predominant clustered spoligotypes identified were SIT 149, SIT 21, SIT 26, SIT 53, and SIT 52, each consisting of 17.6, 13.3, 8.4, 7.4, and 5%, respectively. Lineage 3 and lineage 4, as well as the age group (15–24), were associated significantly with clustering. Conclusion The MTBC isolated from TB patients in Somali region were highly diverse, with considerable spoligotype clustering which suggests active TB transmission. In addition, the Beijing spoligotype was isolated in relatively higher frequency than the frequencies of its isolation from the other regions of Ethiopia warranting the attention of the TB Control Program of the Somali region.